Reflexões sobre o ensino da arte na formação de alunos dos anos iniciais do ensino fundamental - MENDES, Rayara Rodrigues (2025)
The teaching of Art in the school environment aims to awaken the creative, imaginative, expressive and critical potential in students, however, there are many complications that imply the achievement of this process, considering this, the objective of this study seeks to reflect on the importance directed to the teaching of Art for the formation of the child of the initial years stand out in the delineation of the pedagogical strategies incorporated in the study routine of the students of the 5th year (A) of the Municipal School of Childhood and Elementary Education Professora Nair Maia Vieira Gomes, located in the municipality of Tomé-Açu/PA. The problem is centered on the following question: What is the importance of art teaching for the education of children in the early years, implicit and explicit in the pedagogical actions of the Municipal School of Early Childhood and Elementary Education Professor Nair Maia Vieira Gomes, located in the municipality of Tomé-Açu/PA? The methodology is based on a qualitative approach, associated with bibliographical research and field research, and is related to an experience of scientific initiation on the teaching of Art, developed at the aforementioned school. The data collection instruments consisted of using the research techniques of participant observation and semi-structured/non-directive interviews. The theoretical framework included the following theorists: Barbosa (1975-2001-2002-2008); Silva (1989) Ferão et al. (2001); Ferraz and Fusari (2009); Freire (2011); Rodrigues (2013); Chirinéa and Brandão (2015); Iavelberg; Martins, Picosque e Guerra (2010), and documents referring to the Lei de Diretrizes e Bases da Educação Nacional and a Resolution CNE/CP n° 1, of 15 may, 2006. According to the observation made at the School about the teaching of art, as well as its importance in the formation of the child, it is concluded that art, a compulsory subject in the school curricuçum, is being put on the back burner by the School, in view of the emphasis directed towards SAEB preparation, a fact that has negatively impacted the development of the artistic formation of the students, depriving them of having classes during almost every School semestre observed.